Complex dynamics in susceptible-infected models for COVID-19 with multi-drug resistance. (November 2020) - Matouk, A.E.
Highlights: Complex dynamics in a susceptible-infected (SI) model for COVID-19 with multi-drug resistance (MDR) and its fractional-order counterpart are investigated. New fractional Routh-Hurwitz (FRH) conditions are introduced and proved for the fractional case (0, 2]. Local stability of the new SIMDR model is investigated for all the multi-drug resistance steady sates using the FRH scheme. Chaotic attractors are obtained in both the integer and fractional-order SIMDR models. This study helps to understand complex behaviors and predict spread of severe infectious diseases such as COVID-19. Abstract: Nowadays, exploring complex dynamic of epidemic models becomes a focal point for research after the outbreak of COVID-19 pandemic which has no vaccine or fully approved drug treatment up till now. Hence, complex dynamics in a susceptible-infected (SI) model for COVID-19 with multi-drug resistance (MDR) and its fractional-order counterpart are investigated. Existence of positive solution in fractional-order model is discussed. Local stability based on the fractional Routh-Hurwitz (FRH) conditions is considered. Also, new FRH conditions are introduced and proved for the fractional case (0, 2]. All these FRH conditions are also applied to discuss local stability of the multi-drug resistance steady states. Chaotic attractors are also found in this model for both integer-order and fractional-order cases. Numerical tools such as Lyapunov exponents, Lyapunov spectrum and bifurcation diagrams are employed to confirm existence of these complex dynamics. This study helps to understand complex behaviors and predict spread of severe infectious diseases such as COVID-19.